PERALIHAN MATA PENCAHARIAN SEBAGAI BENTUK ADAPTASI (Studi Kasus: Desa Batu Belubang, Bangka) - Ira Adiatma; Azis Nur Bambang; Hartuti Purnaweni (TEKNIK, 2013)
Bangka island as a whole has undergone a significant change related thereto. Group of fishermen coastalcommunities are the most vulnerable to changing weather and coastal environment. In the village of BatuBelubang, frequent extreme weather phenomena of the cyclone and the rapid change of weather, had forced thepopulation to adapt to climate change. The livelihoods of fishermen who rely heavily on natural conditions causethe dependence on weather patterns and ocean activities.This research uses qualitative analysis with the positivistic approach. The method of data collection is done withthe interview focused and observational field to see the real conditions and survey agencies to obtainpreliminary data regarding the level of climate change that occurred in the region. The analysis is done byassessing the linkages/relationship of the destructive effects of climate change on livelihoods of fishermen.From the analysis carried out, the main reason for the occurrence of the transition is economic livelihood. Thistransition is triggered by vulnerability due to climate change and the existence of externalities, namely adeterioration of Tin prices and the pepper in the international market in 1990 which was then backed up bypolicy changes after regional autonomy in 2001. The welfare obtained from short-term floating mines have hugeconsequences for the coastal environmental damage that would lead to a condition in which a new vulnerability.Key words : the transition of livelihood, adaptation, fisherman